Vaccine-Induced CD107a(+) CD4(+) T Cells Are Resistant to Depletion following AIDS Virus Infection - Terahara, Kazutaka (J Virol, 2014)
CD4(+) T-cell responses are crucial for effective antibody and CD8(+) T-cell induction following virus infection. However, virus-specific CD4(+) T cells can be preferential targets for human immunodeficiency virus (HIV) infection. HIV-specific CD4(+) T-cell induction by vaccination may thus result in enhancement of virus replication following infection. In the present study, we show that vaccine-elicited CD4(+) T cells expressing CD107a are relatively resistant to depletion in a macaque AIDS model. Comparison of virus-specific CD107a, macrophage inflammatory protein-1β, gamma interferon, tumor necrosis factor alpha, and interleukin-2 responses in CD4(+) T cells of vaccinated macaques prechallenge and 1 week postchallenge showed a significant reduction in the CD107a(−) but not the CD107a(+) subset after virus exposure. Those vaccinees that failed to control viremia showed a more marked reduction and exhibited significantly higher viral loads at week 1 than unvaccinated animals. Our results indicate that vaccine-induced CD107a(−) CD4(+) T cells are depleted following virus infection, suggesting a rationale for avoiding virus-specific CD107a(−) CD4(+) T-cell induction in HIV vaccine design. IMPORTANCE Induction of effective antibody and/or CD8(+) T-cell responses is a principal vaccine strategy against human immunodeficiency virus (HIV) infection. CD4(+) T-cell responses are crucial for effective antibody and CD8(+) T-cell induction. However, virus-specific CD4(+) T cells can be preferential targets for HIV infection. Here, we show that vaccine-induced virus-specific CD107a(−) CD4(+) T cells are largely depleted following infection in a macaque AIDS model. While CD4(+) T-cell responses are important in viral control, our results indicate that virus-specific CD107a(−) CD4(+) T-cell induction by vaccination may not lead to efficient CD4(+) T-cell responses following infection but rather be detrimental and accelerate viral replication in the acute phase. This suggests that HIV vaccine design should avoid virus-specific CD107a(−) CD4(+) T-cell induction. Conversely, this study found that vaccine-induced CD107a(+) CD4(+) T cells are relatively resistant to depletion following virus challenge, implying that induction of these cells may be an alternative approach toward HIV control.